Genetic Variation of Growth and Selected Wood Properties of Four-Year Old Acacia Auriculiformis Provenances at Serdang, Malaysia - Mahat, Mohd Noor (1999)
A trial at Universiti Putra Malaysia (UPM) Serdang, Malaysia consisting of twenty eight provenances of Acacia auriculiformis A. Cunn. ex. Benth was assessed at four years for total height, diameter at breast height, specific gravity and fibre length. Of these provenances, 7 were from Queensland (QLD), 15 from the Northern Territory (NT) and 6 from Papua New Guinea (PNG). The provenances and geographic regions differed significantly at p < 0.05 in their growth performance. Generally the Queensland provenances recorded the best growth in both height and diameter followed by the Northern Territorry and Papua New Guinea Provenances. The mean total heights for provenances from Queensland, Northern Territory and Papua New Guinea were 13.38 m, 12.37 m and 11.89 m respectively. The mean diameters at breast height for provenances from Queensland, Northern Territory and Papua New Guinea were 12.67 em, 11.04 em and 10.69 em respectively. A similar pattern of variation was found in the wood properties except for wood specific gravity where there was no significant difference encountered between the three geographic regions. However, there were significant variation between provenances on both wood properties studied. The mean specific gravity ranged from 0.53 for the provenance from Balamuk on Bensbach (PNG) to 0.61 for the provenance from South Balamuk (PNG). The mean fibre length ranged from 0.865 mm for the provenance from Balamuk on Bensbach (PNG) to 0.993 mm for the provenance from eoen River (QLD).